MENTZ, Frans Engelbertus Inventory of documents - MENTZ, Frans Engelbertus (ARCA, 2018)
Private papers of F.E. Mentz, National Party MP Westdene [1943-1961]; Deputy Minister Bantu Administration and Development [1958-1960].
COVERAGE 1948-1968; 6 Files; 0,11 Metre.
Keywords: MENTZ, Frans Engelbertus Inventories; Politicians; National Party